Digital Media in English Learning For Tourism in Majene: An Applied Linguistics Study - Januarti Putri, Andi Mega; Imansari, Nurul (ELLITE: Journal of English Language, Literature, and Teaching, 2024)
This study investigates the impact of digital media, particularly AI Fully-Fluent and Instagram, on enhancing Speaking skills for tourism in the English Education program at Universitas Sulawesi Barat. Recognizing the crucial role of English proficiency in maximizing tourism potential, especially in culturally rich regions like Majene, this research addresses the need to improve human resource competencies. The study employs descriptive quantitative approach from applied linguistic perspective, with a sample of 25 students selected through convenience sampling. Data collection involved tests to assess the improvement in Speaking ability after the application of digital media, paired sample t-test with SPSS was utilized in data analysis. Findings reveal positive impact of digital media, with a two-tailed significance value of less than 0.05. Comprehension showed highest improvement, followed by pronunciation, grammar, and fluency. Interactive features of AI Fully-Fluent and Instagram provide a supportive environment for students to practice English, build confidence, and engage in meaningful language use, aligning with interactionist theory in linguistics, which emphasizes the importance of interaction, feedback, and practice in linguistic acquisition. The study offers insightful perspective into the role of digital media in enhancing language learning and tourism, with implications for developing human resources and promoting Majene as tourist destination.